Amorphous Extracellular Eosinophilic Material – The Diagnostic Challenge in Histopathology - P. Sivakumar; P. Rajkumar; S. K. Sridevi; L. Priyadharshini; M. Elancheran (Current Medical Issues)
Amyloidosis encompasses a diverse group of conditions characterized by the extracellular accumulation of misfolded, insoluble proteinaceous material with a cross-beta-pleated sheet structure, leading to organ damage. Due to its varied origins and manifestations, different diagnostic tools are required for accurate diagnosis. A definitive diagnosis is achieved through biopsy, revealing amyloid deposits in the affected tissue. When stained with hematoxylin and eosin, amyloid material appears as amorphous eosinophilic acellular deposits. These morphological features are shared with other substances such as collagen, fibrin, plasma, hyaline globules, hyalinization, and necrosis, posing a diagnostic challenge for pathologists. However, morphology, surrounding tissue morphology, and special stains can differentiate between amyloid and amyloid-like material. This case series of six cases highlights the appropriate staining techniques for differentiating amyloid from amyloid-like material in histopathology.